2007
DOI: 10.1063/1.2431806
|View full text |Cite
|
Sign up to set email alerts
|

Doubly resonant three-wave-mixing spectroscopy of a chiral coupled-chromophore system in solution: Coherent two-dimensional optical activity spectroscopy

Abstract: Theoretical descriptions of doubly resonant two-dimensional (2D) sum-frequency-generation (SFG) and difference-frequency-generation (DFG) spectroscopies of coupled-chromophore systems are presented. Despite that each electronic or vibrational chromophore is achiral, the interaction-induced chirality of a coupled multichromophore system in solution can be measured by using the doubly resonant 2D three-wave-mixing (3WM) spectroscopic method. An electronically coupled dimer, where each monomer is modeled as a sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…70 Cheon et al pointed out that the 2D technique with the even-order susceptibility carries information on the chiral couplings. 75 The surface-specific 2D experiment was conducted on the model membrane system by using the IR-IR-IR-Visible pulse configuration. 76,77 The applications of these surface-specific 2D techniques to the water/lipid interface will provide a new experimental tool for probing the information on the intermolecular coupling of interfacial water.…”
Section: Discussionmentioning
confidence: 99%
“…70 Cheon et al pointed out that the 2D technique with the even-order susceptibility carries information on the chiral couplings. 75 The surface-specific 2D experiment was conducted on the model membrane system by using the IR-IR-IR-Visible pulse configuration. 76,77 The applications of these surface-specific 2D techniques to the water/lipid interface will provide a new experimental tool for probing the information on the intermolecular coupling of interfacial water.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that the numerically simulated 2D IR-IR SFG spectrum is highly sensitive to the peptide secondary structure including dipeptide and polypeptides. 25,26 In this paper, we shall also show that the 2D IR-IR SFG spectroscopy can be of use to distinguish conformational difference between an anti-parallel b-sheet and a parallel b-sheet. 26 To demonstrate the usefulness of 2D IR-IR SFG, we considered three representative helical structures, i.…”
Section: Simulation Study Of 2d Ir-ir Sfg Spectroscopymentioning
confidence: 86%
“…Recently, novel 2D optical spectroscopic methods using circularly polarized beams were theoretically proposed and shown to be useful in measuring the nonlinear optical activity of chiral molecules in an isotropic medium. [23][24][25][26][27][28][29][30] It has been known that the three-wave mixing (3WM) is the lowest-order nonlinear optical response of a molecular system on surface or at interface where the centrosymmetry is broken. [31][32][33][34] Shen and coworkers [35][36][37][38][39][40][41][42][43] showed that the IR-vis (IV) SFG spectroscopy is an incisive surface-specific vibrational spectroscopy, where the IR pulse is used to create vibrational coherence state and the electronically non-resonant visible pulse is Raman-scattered to generate the IR+vis sum frequency field.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations